Description of Knowledge and Attitude of Prospective Hajj Pilgrims KBIH Mandiri 2019 in Malang City About Hypertension - riskiyah, riskiyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
ABSTRACTHypertension is one of the diseases that can cause peopleâ€™s death and it usually does not give any symptoms. Hypertension often occurs to the pilgrims. Knowledge and proper attitudes about hypertension of prospective pilgrims from Indonesia, especially in Malang city (East Java), are expected to reduce morbidity and mortality rates because they can manage their illness, properly. The purpose of this study is to describe the level of hypertension-related knowledge and attitudes of prospective pilgrims from KBHI 2019. The method used in this study is a descriptive cross-sectional study. 48 participants have participated in this study. They are the 2019 pilgrims from Indonesia. The results showed that 18 people (38%) had good knowledge about hypertension, 17 people (35%) are intermediately educated and 13 people (27 %) are lack of knowledge. Furthermore, this study has indicated that 25 people (52%) have positive attitudes and 23 people (48%) have negative attitudes about hypertension. This study concluded that in the majority, the 2019 prospective pilgrims from Malang have good knowledge and acceptable attitudes about hypertension.Keywords:Â Hajj pilgrims, hypertension, knowledge, attitudeÂ